Răspuns :
[tex]S = \frac{1}{2} + {2}^{ - 1} + 2 + {( - 2)}^{1} + {( - 2)}^{2} [/tex]
[tex]S = \frac{1}{2} + \frac{1}{2} + 2 - 2 + 4[/tex]
[tex]S = \frac{1 + 1}{2} + 0 + 4[/tex]
[tex]S = \frac{2}{2} + 4[/tex]
[tex]S = 1 + 4[/tex]
[tex]S = 5[/tex]
[tex]S = \frac{1}{2} + \frac{1}{2} + 2 - 2 + 4[/tex]
[tex]S = \frac{1 + 1}{2} + 0 + 4[/tex]
[tex]S = \frac{2}{2} + 4[/tex]
[tex]S = 1 + 4[/tex]
[tex]S = 5[/tex]
S = \frac{1}{2} + {2}^{ - 1} + 2 + {( - 2)}^{1} + {( - 2)}^{2} S = \frac{1}{2} + \frac{1}{2} + 2 - 2 + 4 S = \frac{1 + 1}{2} + 0 + 4 S = \frac{2}{2} + 4 S = 1 + 4 S = 5